2021
DOI: 10.3390/catal11050638
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Nucleic Acid Modulation for Functional Nanozyme

Abstract: Nanozymes have the potential to replace natural enzymes, so they are widely used in energy conversion technologies such as biosensors and signal transduction (converting biological signals of a target into optical, electrical, or metabolic signals). The participation of nucleic acids leads nanozymes to produce richer interface effects and gives energy conversion events more attractive characteristics, creating what are called “functional nanozymes”. Since different nanozymes have different internal structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…The mechanism of NTP affecting Pr 6 O 11 NRs in oxidizing ABTS was probably due to the coordination and hydrolysis of NTP on Pr 6 O 11 (Figure e). Due to the high oxygen mobility of Pr 6 O 11 , , as well as abundant defects on the nanorod surface, including oxygen vacancies and Pr 3+ /Pr 4+ , Pr 6 O 11 was able to catalyze the oxidation of ABTS efficiently. , It is well known that attachment of nucleic acids can modulate functionalities of nanozymes such as Fe 3 O 4 , CeO 2 , etc. , Many mechanisms, sometimes seemingly contradictory, have been proposed to account for the effects of nucleic acid on tuning oxidase-like activities . Here, we believe the boosting effect of NTP was due to its hydrolysis on Pr 6 O 11 NRs and the consequential free energy release (Δ G ) from it (Figure e).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The mechanism of NTP affecting Pr 6 O 11 NRs in oxidizing ABTS was probably due to the coordination and hydrolysis of NTP on Pr 6 O 11 (Figure e). Due to the high oxygen mobility of Pr 6 O 11 , , as well as abundant defects on the nanorod surface, including oxygen vacancies and Pr 3+ /Pr 4+ , Pr 6 O 11 was able to catalyze the oxidation of ABTS efficiently. , It is well known that attachment of nucleic acids can modulate functionalities of nanozymes such as Fe 3 O 4 , CeO 2 , etc. , Many mechanisms, sometimes seemingly contradictory, have been proposed to account for the effects of nucleic acid on tuning oxidase-like activities . Here, we believe the boosting effect of NTP was due to its hydrolysis on Pr 6 O 11 NRs and the consequential free energy release (Δ G ) from it (Figure e).…”
Section: Resultsmentioning
confidence: 86%
“…28,29 Many mechanisms, sometimes seemingly contradictory, have been proposed to account for the effects of nucleic acid on tuning oxidase-like activities. 30 Here, we believe the boosting effect of NTP was due to its hydrolysis on Pr 6 O 11 NRs and the consequential free energy release (ΔG) from it (Figure 2e). Pr 6 O 11 NRs may catalyze and assist the hydrolysis of NTP, generating free phosphate (P i ) ions.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…In recent years, the scientific community has witnessed the combination and development of nucleic acids and nanozymes, as nucleic acids can compensate for the deficiencies of nanozymes by improving the control over the catalytic activity. [ 75 ] For example, Wang et al [ 76 ] reported that ssDNA adsorbed on g‐C 3 N 4 NSs could improve the catalytic activity of the nanosheets. On the basis of their previous theoretical and experimental results, Wu et al [10a] presented a redox‐modulatory ceria‐nanozyme‐reinforced self‐protecting hydrogel (PCN‐miR/Col) by simultaneously reshaping the hostile oxidative wound microenvironment into a regenerative one and ensuring the structural integrity of the encapsulated proangiogenic miRNA in the oxidative microenvironment (Figure 5d).…”
Section: Therapeutic Strategies Of Enzyme‐based Materials For Wound H...mentioning
confidence: 99%
“…The nanozymes currently used in biomedicine can be simply divided into four groups—peroxidases, oxidases, superoxide dismutases (SODs), and catalases (Ding et al, 2020). Compared with natural enzymes, nanozymes have the advantages of high stability, low cost, and multifunctionality (Cao et al, 2021; Wang, Xu, et al, 2021). Several types of MOFs have been widely used as nanozymes in medicine, including zeolite imidazolate frameworks (ZIFs), isoreticular metal–organic frameworks (IRMOFs), materials of Institute Lavoisier (MILs), and porous coordination networks (PCNs), among others (Hu et al, 2021; Meng et al, 2020; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%